2019
DOI: 10.3389/fnhum.2019.00189
|View full text |Cite|
|
Sign up to set email alerts
|

Touching! An Augmented Reality System for Unveiling Face Topography in Very Young Children

Abstract: Developmental body topography, particularly of the face, is a fundamental research topic in the current decade. However, empirical investigation of this topic for very young children faces a number of difficulties related to the task requirements and technical procedures. In this study, we developed a new task to study the spatially-sensed position of facial parts in a self-face recognition task for 2.5- and 3.5-year-old children. Using the technique of augmented reality (AR) and 3D face tracking technology, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Most children successfully completed 30 trials, regardless of age (t(28) = -1.57, p = .13, n.s.). This result is consistent with our previous study 15 . This suggests that we were able to maintain the motivation of the participants during the whole-body version.…”
Section: Number Of Executed Trialssupporting
confidence: 94%
See 1 more Smart Citation
“…Most children successfully completed 30 trials, regardless of age (t(28) = -1.57, p = .13, n.s.). This result is consistent with our previous study 15 . This suggests that we were able to maintain the motivation of the participants during the whole-body version.…”
Section: Number Of Executed Trialssupporting
confidence: 94%
“…First, the experimental procedure, especially for trial repetition, must be sophisticated. We updated the gamification procedure 15 with AI-based online bone estimation using Microsoft Kinect (an infrared sensor device) to Openpose (an image processing library) 16 . In this study, we used Openpose to extend the targeted body parts from the face to the whole body.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that about half of the 2.5 years old children and 80% of the 3.5 years old children could perform more than 30 correct trials (37 was the maximum). Furthermore, the analysis of detection errors suggested the uniqueness of spatial knowledge of self-face in young children, thus confirming the effectiveness of this new paradigm for studying body image development (Miyazaki et al 2019).…”
Section: Recognizing the Mirror Recognizing Oneself In The Mirrormentioning
confidence: 53%
“…With regard to face image development, a study investigated the spatial location of different parts of one's face in children with 2.5 or 3.5 years of age by using augmented reality and 3D face-building technology (Miyazaki et al 2019). Participants had to locate a sign on their body that they saw in the real-time video in front of them and received a "cheerful" visual and auditory reward in case of correct detection.…”
Section: Recognizing the Mirror Recognizing Oneself In The Mirrormentioning
confidence: 99%
“…For instance, visual cues are used to teach social skills [24,26,30]. Gamification is used to elicit pretend play [4,37], mapping technology is used to train facial recognition [29,38], and trigger-based modeling is used for education purposes to teach vocabulary [27] and reading [18]. AR-based intervention differentiates itself from traditional interventions in its ability to bridge the gap between physical and virtual worlds [26].…”
Section: Related Workmentioning
confidence: 99%